Spiritual care experiences of nurses working in intensive care units: A qualitative study - Dural, Gul (Wiley, 2024)
Aims and ObjectiveThis study was conducted to find out the spiritual care experiences of nurses working in intensive care units.BackgroundMost nurses working in intensive care units are unprepared to provide spiritual care to patients and they lack the competence and skills to provide spiritual care. Lack of moral evaluation of patients has negative effects on the patient. Spiritual care given to patients has effects on patient-nurse communication, general condition of the patient, and the quality of care.DesignA qualitative descriptive design was used.MethodThe study was carried out with 14 nurses who were working in the intensive care units of a university hospital in eastern Turkey between May and July 2022. Two forms were created by the researcher according to the purpose of the study and the population. Inductive thematic analysis was used to evaluate the data. Ethics committee approval was obtained.ResultsTen of the nurses were women. Their ages were between 25 and 47 years, their working years ranged between 2 and 28 years, and their weekly working hours ranged between 40 to 56 hours. As a result of the thematic analysis, six themes and 18 sub-themes were determined: The themes determined are (1) Definition of spiritual care (2) Time of spiritual care, (3) Benefits of spiritual care, (4) Spiritual care practices, (5) Obstacles in providing spiritual care.ConclusionsProviding spiritual care to patients in intensive care is a very important experience for nurses. Understanding spiritual care, recognizing its importance, and including it in nursing practice have a central significance.Relevance to Clinical PracticeSpiritual care provided in nursing profession is as important as physical care, and supporting patients in intensive care is at the heart of providing the best holistic care.
Keywords: experience; intensive care units; spiritual care